Dua Dimer Resveratrol dari Kulit Batang Shorea parvifolia (dipterocarpaceae) - Rosyidah, Kholifatu; Juliawati, Lia Dewi; Syah, Yana Maolana; Hakim, Euis Holishotan; Achmad, Sjamsul Arifin; Makmur, Lukman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
Two resveratrol dimers, (-)-ampelopsin F dan (-)-laevifonol were isolated from aceton extract of the stem bark ofShorea parvifolia. The structures of these compounds were determined based on their spectroscopic data includingspectroscopy ultra violet (UV), infra red (IR), nuclear magnetic resonance (1H-NMR, 13C-NMR) and also were comparedto the reported data.